EFFICACY OF ELECTRICAL STIMULATION (ES) ON DYSPHAGIA IN POST-STROKE PATIENTS: A SYSTEMATIC REVIEW - Modesty, Kyra; Sitepu, Brigitta Ellycia; Budianto, Pepi; Probandari, Ari; Tandiyo, Desy Kurniawati (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Stroke is a disease that can occur in both developed and developing countries and is the second leading cause of death in the world. Stroke can cause various complications such as dysphagia. This study examines the efficacy of electrical stimulation (ES) as a treatment for dysphagia in post- stroke patients with various measurements of the severity of dysphagia. Objective: This study aims to review the efficacy of electrical stimulation on dysphagia in post-stroke patients. Methods: This study uses a systematic review method by following the guidelines from PRISMA. Articles are arranged based on keywords that have been determined in PICO, namely electrical stimulation, dysphagia, and stroke. Articles included in the inclusion criteria are RCTs, in English, and published between January 2013 and January 2023. Results: Eighteen studies that met the inclusion criteria were critically reviewed by the two authors. There were ten types of outcomes included in this systematic review and six of them had significant results for reducing the severity of dysphagia. Conclusion: ES can be given as the main therapy for post-stroke dysphagia patients. The six types of outcomes used to measure the degree of dysphagia, namely FOIS, PAS, FDS, PTT, OTT, and MASA, showed high significance associated with a reduction in the degree of dysphagia thereby reducing the risk of aspiration pneumonia by using this ES therapy.